Study of The Processing and Financial Analysis of Berembang Fruit (Sonneratia caseolaris) as Food and Drink Material in Deli Serdang Regency - Inggrid Tarihoran; Agus Purwoko; Kansih Sri Hartini (Peronema Forestry Science Journal, 2013)
Utilization of mangrove fruit become to food and drink very rarely published. One of mangrove fruit used was fruits of Sonneratia caseolaris.Not many peoples know about these berembang fruits processing but the people in the lictoral Deli Serdang has begun berembang fruits processing as material food and drink. This research aims to determine berembang fruit processing as material food and drink, to determine the financial feasibility berembang fruit processing, and to determine for berembang fruit processing development of strategy. To determine the berembanng fruit processing is done by interview and questionnaire, while for financial using cost and value analysis, Revenue Cost Ratio (R/C) analysis, Payback Period (PP) analysis, Break Event Point (BEP) analysis and for  development of strategy using by SWOT analysis. The result showed in traditional that processing of berembang fruit, while the results of the financial analysis known that berembang fruit processing become a lunkhead and syrup are feasible because of the R/C ratio greater than one (1,39 and 1,42). Based on the strategy SWOT, the most strategy needed was WO strategy. PP lunkhead and syrup of 4.9 and 4.3 and BEP production volumeof lunkhead and syrup of (72 and 73 units) are still below the production volume of 100 units. Based on the SWOT strategy, a strategy that is needed is a strategy ST, WT, SO, and WO. Key words : Sonneratia caseolaris, financial analysis, berembang fruit, SWOT analysis